Laparoscopy of a splenic flexure volvulus - Yuichi Sesumi; Toshio Sawai; Shohei Maekawa; Hideki Yoshida; Makoto Yagi (Elsevier, 2017)
Splenic flexure volvulus (SFV) is a very rare condition that is unlikely to be suspected even when a patient has repeated episodes of abdominal pain and dyschezia. We describe the case of SFV diagnosed and treated laparoscopically in the non-volvulus condition. A 14-year-old boy with no medical history had severe left upper abdominal pain and dyschezia for approximately 1 year. Although contrast enema examination revealed no characteristic findings of volvulus, such as a bird-beak sign, a redundant part of the colon was found to be the site of abdominal pain. We suspected that this part of the colon was the cause of the left upper abdominal pain and performed laparoscopic exploration. The colon at the splenic flexure formed a long loop and was predisposed to twisting; therefore, we performed resection and functional anastomosis of this redundant colon. The postoperative course was uneventful, and the left upper abdominal pain and dyschezia did not recur. Laparoscopic exploration can play a role in patients who are suspected to have recurrent colonic volvulus with radiographic evidence of a redundant portion of the colon, as indicated in our case. Keywords: Splenic flexure volvulus, Child, Laparoscopy